Effectiveness of internet-delivered dialectical behavior therapy skills training on executive functions among college students with borderline personality traits: a non-randomized controlled trial - CV Vijayapriya; Rameshbabu Tamarana (Research in Psychotherapy, 2023)
Given the enormous influence of emotions on cognitive processes, individuals with borderline personality disorder (BPD) suffer from marked deficits in higher-order thinking abilities. Considering the prevalence of BPD among college students, this study aimed to investigate the changes in perceived executive functioning among college students with traits/presence of BPD undergoing internet-delivered dialectical behavior therapy skills training (DBT-ST) that included the mindfulness and emotion regulation modules. An internet-delivered version of DBT-ST was opted for, as technological advancements in the present era promote the use of online platforms for psychotherapy. This non-randomized controlled trial consisted of 36 college students with traits/presence of BPD. The intervention group attended 13 sessions of DBT-ST, and the control group attended 13 sessions of behavioral activation. Perceived executive functioning was assessed using the Behavior Rating Inventory of Executive Functions for Adults. A 2-way repeated measures analysis of variance was used to evaluate the treatment impact on the outcome variable. Results showed that the DBT-ST group had larger improvements in their abilities to initiate, plan, and organize current and future-oriented task demands and to organize their everyday environment, compared to the control group. Both, the DBT-ST group and the control group demonstrated improvements in emotional control, working memory, and their abilities to shift and task monitor. Findings suggest that the internet-delivered version of DBT-ST, consisting of the mindfulness and emotion regulation modules, can foster notable improvements in executive functions among college students with traits/presence of BPD. Improved executive functioning is one of the several multifaceted outcomes of dialectical behavior therapy.